Icariside II Attenuates Chronic Hydrocephalus in an Experimental Subarachnoid Hemorrhage Rat Model - Ce Dong; Xing Ming; Zhanying Ye; Pengfei Wang; Lin Wang; Zheng Li; Baogen Pan (Frontiers Media S.A., 2018)
Purpose To investigate the role of ICA II in subarachnoid hemorrhage (SAH)-  related chronic hydrocephalus. Methods A two hemorrhage injection model of SAH was created in Sprague Dawley rats (6-8 weeks). A total of 125 rats were randomly assigned into five groups: Sham group, SAH group, SAH+ ICA II (1 mg/kg) group, SAH + ICA II (5 mg/kg) group, and SAH + ICA II (10 mg/kg) group. TGF-β1, phospho-Smad2/3, connective tissue growth factor (CTGF), and procollagen type I carboxy-terminal propeptide (PICP) were assessed via real-time PCR, Western blotting, and enzyme-linked immunosorbent assay. Lateral ventricular index, Masson staining, and Morris water maze tests were employed to evaluate subarachnoid fibrosis, hydrocephalus, and long term neurological function following SAH. Results ICA II (1, 5, 10 mg/kg) inhibited subarachnoid fibrosis, attenuated ventriculomegaly, and effectively suppressed SAH related chronic hydrocephalus. In addition, parallel reduced expression of members of the TGF-β1/Smad/CTGF signaling pathway were observed. Importantly, ICA II may improve long term neurocognitive deficits after SAH. Conclusion ICA II might suppress fibrosis via inhibition of TGF-β1/Smad/CTGF pathway, prevent the development of SAH related chronic hydrocephalus, and improve long term neurocognitive defects following SAH.